Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1104/pp.113.2.431
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde Is a Causal Agent Responsible for Ethanol-Induced Ripening Inhibition in Tomato Fruit

Abstract: Inhibition of tomato (Lycopersicon esculentum Mill.) fruit ripening by exogenously applied ethanol was shown to be caused by elevated endogenous levels of acetaldehyde (AA). Exposure of excised pericarp discs of mature-green tomato fruit to ethanol or AA vapors produced elevated levels of both compounds in the tissue, but only the levels of AA were associated with ripening inhibition. Ripening inhibition was dependent on both the applied concentration and the duration of exposure. Discs treated with inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 17 publications
(18 reference statements)
2
18
1
1
Order By: Relevance
“…Acetaldehyde has previously been shown to inhibit softening in peach and tomato (Lurie and Pesis, 1992;Pesis and Marinansky, 1993;Beaulieu et al, 1997). The inhibition of avocado softening by AA vapour is similar to that caused by low O 2 treatment or by ethanol vapour Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Acetaldehyde has previously been shown to inhibit softening in peach and tomato (Lurie and Pesis, 1992;Pesis and Marinansky, 1993;Beaulieu et al, 1997). The inhibition of avocado softening by AA vapour is similar to that caused by low O 2 treatment or by ethanol vapour Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Besides this, high CO 2 and/or low O 2 within the atmosphere of the fruit can induce anaerobic metabolism resulting in enhanced accumulation of ethanol and acetaldehyde (Kader 1987). Ethanol and acetaldehyde were in fact reported to delay the ripening of tomato fruit (Kelly and Saltveit 1988;Beaulieu et al 1997). This thereby explains the reason behind the retardation of ripening process due to short period of anaerobiosis treatment prior to the storage of tomato fruits as observed by Kelly and Saltveit (1988), Pesis and Marinansky (1993) and Paul and Srivastava (2006).…”
Section: High Carbon Dioxidementioning
confidence: 88%
“…It was therefore suggested that it is the acetaldehyde and not the ethanol which is the causal agent for ethanol-induced inhibition of fruit ripening. Later on, it was in fact found to be true because it was only the level of acetaldehyde which was found to be associated with inhibition of ripening by Beaulieu et al (1997). In light of above findings, it was concluded by Pesis (2005) that ethanol and acetaldehyde are natural compounds that are essential in governing the process of fruit ripening.…”
Section: Acetaldehydementioning
confidence: 97%
See 1 more Smart Citation
“…So, it was concluded that mandarins accumulate larger amount of acetaldehyde and ethanol in comparison to grapefruit and this was because of higher activity of the enzyme ADH in the juice sacs in view of the lesser permeability of the peel towards the exit of gases in mandarins (Shi et al 2007). In this regard it is interesting to note that ethanol and acetaldehyde have already been reported to delay ripening in tomato and other fruits (Beaulieu et al 1997;Pesis 2005;Pesis 2006). …”
Section: Fruit Ripeningmentioning
confidence: 98%